Furthering financial inclusion through retail asset management in South Africa - Steppe, Grant Michael (My University, 2018)
This study looks to increase the level of financial inclusion in South Africa by providing insight around the local savings environment and in particular the unit trust industry. The study therefore looks to asses the determinants of unit trust investment in South Africa. Although a large quantity of research has been done in order to better understand savings and financial inclusion in South Africa, relatively little research has been conducted on the role that collective investment schemes play in engendering savings and creating a more financially inclusive environment. Collective investment schemes, such as unit trusts, are an effective way of exposing savings to higher rates of compound interest and should form an integral part of any savings portfolio. The study has found that various elements such as education and the nature of bank account usage have a direct impact on the rate of unit trust investment in the country. This presents an initial step towards better understanding the determinants of unit trust investment in South Africa, but there is still much to be done. The research follows a mixed method approach and used an anonymous survey to gather data from banked South African citizens. It is hoped that the research will go some way towards aiding financial service providers to better understand their customer base in South Africa.
MBA
Keywords: Financial institutions -- South Africa. Microfinance -- South Africa. Financial literacy -- South Africa.